Study of 10В nucleus structure in lithium reactions - Kabatayeva, R.S.; Shaldarbekova, D.; Akhanova, N.; Bolekbayev, B. (Recent Contributions to Physics, 2012)
In this paper we have calculated the spectroscopic factors for the separation of light clusters in core 10B in the multiparticle shell model. We carried out the calculation of excitation spectra of nuclei 10B in the reaction  on the assumption that the basic mechanism is the transfer of a-particles. We calculated excitation spectra of nuclei 10B in the reaction  on the assumption that the basic mechanism is the transfer of tritium cluster. The classification of the mechanisms 6Li(6Li, d)10В and 6Li(7Li, t)10В is carried out.
Keywords: spectroscopic factor; multiparticle shell model